(untitled) (Journal of Universal Science Research, 2023)
In this article, in the years of independence based on the increasing attention to cultural heritage, including the establishment of the Abu-l Mu’in al-Nasafi scientific-research center in Kashkadarya, the goals and tasks of the center and the development of the tourism industry in the region were considered.